RISK ANALYSIS OF HEAVY METAL WEIGHT MERCURY IN SEA SEDIMENT IN THE COASTAL AREAS OF MAKASSAR CITY - Ishak, Nuning Irnawulan (PROMOTIF: Jurnal Kesehatan Masyarakat, 2017)
Monitoring of marine sediments as an indicator of heavy metal mercury pollution in waters has been conducted. This study used an observational design with an Environmental Risk Analysis approach with the objective of knowing the concentration of mercury (Hg) heavy metals and the risk of metal contamination in marine sediments. Sediment sampling was conducted at 10 points in 5 (five) urban villages of Makassar City. The results showed that the highest mercury concentration was in Cambayya Village at 1.871 mg / kg and the lowest mercury concentration was in Lae-Lae Island Kelurahan at 1,550 mg / kg. In general, the content of heavy metals mercury in marine sediments in coastal areas of Makassar City has exceeded the threshold of 0.13 mg / kg with the enormous environmental risk occurring in coastal areas of Makassar City due to exposure to mercury metals, ranging from 11-22 under the risk category high HQ> 10.Keywords : Risk Analysis, Sea Sediments, MercuryÂ Â